Oncology safety of proximal gastrectomy for advanced Siewert II adenocarcinoma of the esophagogastric junction compared with total gastrectomy: a propensity score-matched analysis - Qiying Song; Di Wu; Shihe Liu; Ziyao Xu; Yixun Lu; Xinxin Wang (World Journal of Surgical Oncology)
Abstract Objective The safety of proximal gastrectomy (PG) for the treatment of advanced Siewert II adenocarcinoma of the esophagogastric junction (AEG) remains debatable. In this study, we aim to evaluate the oncological safety of PG and the metastasis rate of key distal lymph node dissection, which is typically excluded in PG. Method This study retrospective collected advanced Siewert II AEG patients who underwent gastrectomy at the First Medical Center of the General Hospital of the People’s Liberation Army (PLA) from January 2014 to December 2019. A total of 421 patients were enrolled, including 237 PG and 184 total gastrectomy (TG). Propensity score matching (PSM) in a 1:1 ratio was performed to reduce the influence of confounding variables. Results After PSM, 153 cases were matched in each group. The TG group had longer operation time, more lymph node detection and longer postoperative hospitalization time than the PG group (Both P < 0.05). The postoperative complications of the two groups were not statistically significant (P > 0.05). For long-term complications, the incidence of reflux esophagitis and anastomotic stenosis were significantly higher in the PG group than in the TG group (Both P < 0.05), but dumpling syndrome and anemia were significantly lower in the PG group compared to the TG group (Both P < 0.05). The 3-year overall survival (OS) and disease-free survival (DFS) between the two groups were no statistically significant difference (OS: 77.4% and 80.9%, P = 0.223; DFS: 69.7% and 76.1%, P = 0.063). Distal lymph node metastasis rates for No.4d, 5, and 6 were all less than 5%, and the therapeutic value index were also relatively low, with values of 1.09%, 3.26%, and 1.45%, respectively. In addition, the distal No.4d, 5, or No.6 lymph node metastasis rates were significantly higher in patients with tumor size ≥ 4 cm and T4 stage (14.29% and 23.40%) than in patients with tumor size < 4 cm and T2-3 (2.78% and 5.11%) (Both P < 0.05). The results of subgroup survival analysis showed that for patients with tumor size ≥ 4 cm or T4 stage, the TG group had better DFS compared with the PG group (HR 0.618, 0.387–0.987, P = 0.044), while no significant survival benefits were observed in other subgroups. Conclusion In summary, for Siewert II AEG with tumor size < 4 cm and T2-3 stage, PG may be a reasonable choice with comparable oncological efficacy to TG. But for higher survival benefits, TG remains gold standard particularly for patients with tumor size ≥ 4 cm or T4 stage.